Determination of the Elastic Constant of the Top Plate of a Cello in the Interaction with the Bridge - PAUPY, Pablo; TABLA, Pablo; HUGGENBERGER, Dario; ELFI, Federico; MOREL, Eneas N.; TORGA, Jorge R. (Archives of Acoustics, 2025)
This paper aims to determine the equivalent static elastic constant of a cello’s top plate in the interaction with the bridge. Experimental results detailing this constant are presented based on measuring the deformation and forces caused by a system of calibrated springs in similar conditions to that obtained when these forces are produced by the action of the strings. Subsequent tests are conducted following an intervention by a luthier to adjust the sound post, with the aim of assessing the impact on the elastic constants.